Pengaruh Disiplin Kerja dan Pelatihan Kerja Terhadap Kinerja Guru SMP Negeri 3 Palembang - Alfarisi, M. Wahyu; Halin, Hamid; Veronica, Meilin (Jurnal EMT KITA, 2023)
Teachers have a role in developing human resources through the educational process, therefore teacher performance must be continuously improved. This study aims to determine the effect of work discipline and job training on teacher performance at SMP Negeri 3 Palembang partially and simultaneously. This study uses a quantitative method in which the data source is obtained from the results of the questionnaire and the data processing technique uses multiple linear regression analysis using SPPS Version 24 with a Likert Scale. The population in this study were civil servant teachers at Palembang 3 Public Middle School as many as 42 respondents. The results of this study concluded that work discipline influences teacher performance with a t-value of 7.383 and a Sig of 0.000. And the job training variable affects teacher performance with a t-value of 2.360 and a Sig of 0.023. While the simultaneous test shows that the variables of work discipline and job training jointly affect teacher performance with a calculated F value of 150.946 and a Sig value of 0.000. And it can be seen from the coefficient of determination that the ability of the variables of Work Discipline (X1) and Job Training (X2) on Teacher Performance (Y) is 88.0%. Therefore, the remaining 12.0% is influenced by other variables not examined in this study.